Pengaruh Perbedaan Frekuensi Pemberian Pakan Buatan terhadap Pertumbuhan Benih Lele Dumbo (Clarias gariepinus L.) pada Balai Benih Ikan Lingsar - Dian Lestari; Nurul Hayati; Muhajir Muhajir (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2026)
Based on data from FAO (Food and Agriculture Organization of The United Nations), it has been predicted that the aquaculture subsector will become one of the most relied-upon resources in the future, especially in meeting food needs, fish-based nutritional needs, and empowering the global community's economy (FAO, 2016). Catfish is a type of freshwater fish that can grow and develop well because it can be cultivated in limited land areas (Marsela, 2018). The frequency of feeding is one of the important factors that need to be considered in catfish farming. To determine the effect of different feeding frequencies on the absolute weight of dumbo catfish, a study was conducted using an experimental design called the Completely Randomized Design (CRD), with 3 treatments and a total of 8 replications. The test treatments were as follows: Treatment 1 (feeding twice a day), Treatment 2 (feeding three times a day), and Treatment 3 (feeding four times a day). The results of the ANOVA test showed a significant value of 0.000 (P < 0.05), indicating a significant difference in each of the different feeding frequencies. The analysis of the Least Significant Difference (LSD) test at a 5% significance level also showed that the relationship between each treatment had a significant value of 0.000 (P < 0.05). The average absolute weight of the fish for Treatment 1 was 12.99 grams, for Treatment 2 was 15.03 grams, and for Treatment 3 was 17.03 grams. The highest growth in the absolute weight of dumbo catfish fry occurred in Treatment 3 (feeding four times a day).